2018
DOI: 10.1002/lary.27457
|View full text |Cite
|
Sign up to set email alerts
|

How does aging affect recognition of spectrally degraded speech?

Abstract: Objectives/Hypothesis: Cochlear implants (CIs) restore auditory sensation to patients with moderate-to-profound sensorineural hearing loss. However, the benefits to speech recognition vary considerably among patients. Advancing age contributes to this variability in postlingual adult CI users. Similarly, older individuals with normal hearing (NH) perform more poorly on tasks of recognition of spectrally degraded speech. The overarching hypothesis of this study was that the detrimental effects of advancing age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 31 publications
(67 citation statements)
references
References 57 publications
2
65
0
Order By: Relevance
“…Nonverbal reasoning has not consistently emerged as a significant predictor of speech recognition in CI users (e.g., Akeroyd; 1 but see Knutson et al; 24 Holden et al) 21 . Moberly et al (2018) 35 found that the strongest neurocognitive predictor of speech recognition among a similar group of CI users was nonverbal reasoning, using the same Raven's Progressive Matrices test as in the present study. In both studies, a timed version of the Raven's test was usedparticipants had to complete as many items as possible within ten minutes.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Nonverbal reasoning has not consistently emerged as a significant predictor of speech recognition in CI users (e.g., Akeroyd; 1 but see Knutson et al; 24 Holden et al) 21 . Moberly et al (2018) 35 found that the strongest neurocognitive predictor of speech recognition among a similar group of CI users was nonverbal reasoning, using the same Raven's Progressive Matrices test as in the present study. In both studies, a timed version of the Raven's test was usedparticipants had to complete as many items as possible within ten minutes.…”
Section: Discussionmentioning
confidence: 55%
“…All of the CI users had participated in a larger study on speech, language, and neurocognitive skills, which, at the time of the present study, included 44 adult postlingually deafened CI users (Moberly et al; 33 Kramer et al; 25 Moberly et al). 35 Of the 21 CI users in the present study, 11 scored within the upper quartile of the distribution (HiPRESTO) and 10 scored within the lower quartile (LoPRESTO) of a group of 44 CI users (overlapping with participant groups reported in earlier studies) on PRESTO, after adjusting for those who did not complete or were unable to complete the SMRT (n ¼ 4). The 11 HiPRESTO CI users included 5 female and 6 male participants, aged 45-70 years (M ¼ 60; standard deviation [SD] ¼ 8), and the 10 LoPRESTO CI users included 4 female and 6 male participants, aged 52-81 years (M ¼ 65; SD ¼ 10).…”
Section: Participantsmentioning
confidence: 47%
See 3 more Smart Citations